Wokół recepcji Traktatu polemicznego Witolda Wirpszy. Głosy o Miłoszu w roku 1951 w świetle dokumentów cenzury - Woźniak-Łabieniec, Marzena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
The aim of this paper is to present the 1951 dicussion on Czesław Miłosz's escape from Poland. Wirpsza's poem, published in January 1951, was dedicated to Czesław Miłosz. It was was commented on in a literary cultural newspaper over the next few months. Miłosz is shown as a deserter and a traitor, who has lost his poetic talent. The analysis of censorship documents shows that instructions for Miłosz's texts and texts about him must have been issued in May 1951.